2014
DOI: 10.3171/2014.7.gks14923
|View full text |Cite
|
Sign up to set email alerts
|

Leksell Gamma Knife radiosurgery of the jugulotympanic glomus tumor: long-term results

Abstract: ObjectGlomus tumors usually display indolent behavior, and the effectiveness of radiation in stopping their growth can be assessed after long-term follow-up. Currently only midterm results of radiosurgery are available, so the authors included patients treated by Gamma Knife at least 10 years ago in this study to obtain a perspective of long-term results.MethodsDuring the period from 1992 to 2003, the Gamma Knife was used to treat 46 patients with glomus tumors. The age of the patients ranged from 21 to 79 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…The overall reported tumor control rate ranges between 62.5% and 100% (Table 4). 35 In this series, we reported the second longest follow-up period, but with a higher mean tumor volume and a lower mean dose to the tumor. 9 However, data are not directly comparable because of different patients' selection criteria, radiosurgical treatment data, and different follow-up methods.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The overall reported tumor control rate ranges between 62.5% and 100% (Table 4). 35 In this series, we reported the second longest follow-up period, but with a higher mean tumor volume and a lower mean dose to the tumor. 9 However, data are not directly comparable because of different patients' selection criteria, radiosurgical treatment data, and different follow-up methods.…”
Section: Discussionmentioning
confidence: 63%
“…Gamma Knife radiosurgery seems to offer better results in terms of tumor control and toxicity, however, the treatment of these tumors has to be tailored on the patients' age and symptoms, tumor volume, and extension. 3,6,9,20,24,31,35,48,52,53 20,24,26,35,50,51 Based on these findings, Gamma Knife radiosurgery can be considered as a primary treatment in almost all cases of glomus tumor, except for those patients experiencing symptoms and signs of intracranial hypertension, or for those patients presenting with huge tumors with caudal extension, that cannot be easily approached only with a Gamma Knife radiosurgery treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Stereotactic radiosurgery may be applied as the treatment of choice [2,3,6,9]. In paragangliomas, this method results in lower morbidity than surgery with a possibility of clinical improvement [3].…”
Section: Discussionmentioning
confidence: 99%
“…It provides a good long-term tumor control, with 61% of the tumors stable in size [3]. Recent studies have shown a long-term neurological improvement in 42% of patients and aggravation of clinical symptoms in 4% of patients treated with stereotactic radiosurgery [911]. …”
Section: Discussionmentioning
confidence: 99%
“…On average, the decrease in size of tumors treated in our study was 37% is comparable to other centers that have studied tumor response to GKRS. 9,12,17,2125 These are slow growing tumors and it is important to follow these tumors over longer periods of time to assess for control of growth.…”
Section: Discussionmentioning
confidence: 99%